Mathematical Connections Based on Self regulated learningon MEAs Learning and Independent Learning with Module Assisted - Rahmawati, Luthfiana; Suyitno, Hardi; Sukestiyarno, Sukestiyarno (Unnes Journal of Mathematics Education Research, 2020)
This study aims to determine the effectiveness Eliciting Activities Models learning and independent learning with module assisted on mathematical connections of students and to know mathematics connection based on self regulated learning. This study uses mixed method with concurrent embedded. Subjects of this study were 7th grade students of MTs Islamiyah Blingoh 2018/2019 school year. In the quantitative stage. random sampling consisted of three classes. Two classes are used for the experimental class and one class is used for the control class. The results showed that the Eliciting Activities Models and independent learning with module assisted was effective against mathematical connection skills. Students with high self regulated learninghave very good connections by fulfilling three indicators. namely the connection between topics in mathematics. the connection between mathematical material and science other than mathematics and the connection between mathematics and everyday life even though there are insignificant errors in connection indicators between mathematical topics. Students with moderate self regulated learninghave good connections by fulfilling two indicators. namely connections between topics in mathematics are mastered with good categories and connections between mathematics and science other than mathematics are mastered by sufficient categories while connections between mathematics and everyday life are controlled in good categories. Students with low self regulated learning cannot attain a good mathematical connection indicator. connections between topics in mathematics and connections between mathematics and science other than mathematics are mastered by fewer categories while connections between mathematics and everyday life are controlled insufficient categories. In Eliciting Activities Models learning and independent learning with modules assisted are better equipped with apperception activities in order to be able to help students in terms of mathematical connections. especially to improve mathematical connection skills. especially students who have low self regulated learning.